Comorbidities and related factors in rheumatoid arthritis patients of south India- Karnataka Rheumatoid Arthritis Comorbidity (KRAC) study - S. Chandrashekara; V. Shobha; B.G. Dharmanand; R. Jois; S. Kumar; K.M. Mahendranath; V. Haridas; S. Prasad; Y. Singh; M.A. Daware; A. Swamy; R. Subramanian; et al. (PAGEPress Publications, 2017)
The aim was to study the prevalence of comorbidities in rheumatoid arthritis (RA) patients in everyday clinical practice and their association with disease-specific and demographic factors. The multi-center study recruited 3,247 (at 14 centers, and 265) were excluded due to incomplete data. The number of subjects considered for the analysis was 2982. The mean (±standard deviation) age was 48.98±12.64 years and the male-to-female ratio was 1:5. The data was collected based on a pre-structured pro forma by trained clinical research associates through interview and verification of charts and reports available in the patient records. The following comorbidities were studied: cardiovascular disease, hypertension, diabetes mellitus, hypercholesterolemia, thyroid disease, psychiatric diseases like depression, and pulmonary disease. Hypertension (20.7%), diabetes mellitus (14.4%) and thyroid disease (18.3%) were the most prevalent comorbidities. Hypercholesterolemia (5.3%), pulmonary diseases (2.1%), cardiovascular diseases (0.2%) and depression (0.03%) were prevalent in ≤5% of the study population. The overall presence of comorbidity increased with age and reduced with the duration of illness prior (DOIP). The age, gender, and DOIP differed significantly between groups with and without hypercholesterolemia. Females had a statistically increased prevalence of thyroid disease. The prevalence of comorbidities in RA patients from south India is around 40% and the incidence of comorbidity increased with age. As per the literature evidence, the prevalence in the current study subjects was higher when compared to prevalence of similar diseases occurring in the general south Indian population.